VOLUNTEER ACTIVITIES, CAN THEY IMPROVE STUDENTS' ETHICAL BEHAVIOR? - Yasa, I Nyoman Putra; Dharmawan, Nyoman Ari Surya (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study generally aims to reveal students' perceptions of tax volunteer activities related to their ethical behavior. This study is qualitative using a case study approach. The informants in this study were tax volunteers from 8 universities in Bali. Data collection was carried out using interview techniques related to ethical perceptions and assessment rubrics related to the assessment of tax volunteer ethics. The final assessment was carried out using an assessment of ethical indicators. The results of this study stated that tax volunteer activities were quite capable of improving students' ethical behavior. Based on the integrity assessment aspect, 2.3% had begun to develop, 83.3% developed and 14.4% were cultured in the ethics of income disclosure, while from the objective side, 100% of respondents had a culture of ethical behavior in terms of understanding tax regulations.